Tumor-Homing of Mesenchymal Stem Cells Infected with Oncolytic Virus in a Canine Patient - Delgado Bonet, Pablo; Tomeo Martín, Beatriz Davinia; Ortiz Díez, Gustavo; Perisé Barrios, Ana Judith (My University, 2022)
Abstract: Intravenous administration of oncolytic adenovirus (OAds) can be challenging, although various vehicles for the delivery of the virus to the tumor have been described. The efficacy of mesenchymal stem cells (MSCs) as a virus vehicle has been reported in mouse models and canine and human patients, but the actual action mechanism has never been described in patients. It is of importance to determine whether MSCs infected with OAds can reach the tumor and release the virus in a clinical setting. For this purpose, GFP-labeled MSCs were infected with an OAd and inoculated into a companion dog diagnosed with spontaneous lung carcinoma. Forty-eight hours later, the tumor was excised and analyzed microscopically by flow cytometry for GFP fluorescence detection, and a cellular culture was established. Peripheral blood samples were taken to quantify the oncolytic adenovirus by qRT-PCR. Green fluorescence cells detected in the cellular culture by microscopy and flow cytometry revealed 0.69% GFP-positive cells in the tumor. OAd in peripheral blood was confirmed by qRT-PCR during follow-up. For the first time, the tumoral-homing capacity of OAds infected-MSC has been confirmed in a clinical setting, helping to explain the clinical response mechanism, whose efficacy was previously reported in canine and human patients. Keywords: Celyvir; oncolytic virus; tumor-homing; virotherapy